Słownictwo medyczne w „Dzienniku Urzędowym Królewskiej Regencyi w Poznaniu” (pierwsza połowa XIX wieku) - Pihan-Kijasowa, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
In the preparation of this article, I resorted to the 19th-century official press, namely, to “Dziennik Urzędowy Królewskiej Regencyi w Poznaniu” (Official Journal of the Royal Regency in Poznań). In the article, I concentrate on medical vocabulary recorded in this source. I understand the term medical vocabulary comprehensively. It comprises the names of: diseases and their symptoms, means of treating them, names of medicines, medical procedures, institutions providing healthcare and distributing medical supplies, names of patients and persons involved in treatment and healthcare. The vocabulary of the semantic-lexical field recorded in the Journal interpreted this way is varied as regards its origin, construction and social provenance. It contains borrowed names, predominantly from Latin and Greek, possessing the status of medical terms, less often from French; it also includes vernacular vocabulary belonging to the general literary or/and professional-medical language as well as some colloquial items. Some of the excerpted medical terms are one-word designations, but a significant part of them are two- or multi-word names. The medical terminology recorded attests to the lexical resource which was commonly known and understood at the time since the magazine was intended for a wide audience and was supposed to inform in a communicative way about current problems, including health-related ones.